Teamwork, Resilience, and Leadership: The Contribution of Sports to the Holistic Formation of Future-Ready Graduates - Mary Rose Montano; Aveto M Dasal Jr; Simplicio P Alba; Ronald A Gonzales; Anna Rhea C Opeña; Meljhon G Mosca (Advanced Qualitative Research, 2026)
The role of sports in higher education extends beyond physical development, fostering essential life skills such as teamwork, resilience, and leadership. This research explores how athletic participation at the City College of Calamba (CCC) contributes to the holistic formation of future-ready graduates. Despite anecdotal evidence supporting the transformative impact of sports, there is limited empirical research on how these experiences shape long-term professional and personal development, particularly in the local context. This research aims to examine the influence of athletic involvement on the personal and professional growth of graduates, focusing on the development of teamwork, resilience, and leadership. It seeks to address gaps in understanding how sports participation equips students with skills that transcend the playing field, aligning with CCC’s mission to produce globally competitive and socially responsible professionals. A qualitative case study design was employed, analyzing responses from 20 alumni (2020–2024) who were student-athletes. Data were collected via Google Forms using open-ended questions, and thematic analysis was conducted following Braun and Clarke’s framework. The study explored themes related to discipline, leadership, resilience, and career readiness, grounded in the participants’ lived experiences. The findings reveal that athletic participation significantly enhances character formation, time management, and emotional resilience. Key themes include the transfer of teamwork skills to professional settings, the development of leadership through shared responsibilities, and the ability to overcome adversity. Graduates reported applying these competencies in education, public service, business management, and technical fields. The study also highlights the need for structured support systems to balance academic and athletic demands. This research contributes to institutional knowledge by demonstrating the long-term benefits of sports participation in higher education. It offers actionable insights for enhancing CCC’s athletic programs, emphasizing leadership development, mental health support, and alumni engagement. The study underscores the value of sports as a co-curricular platform for holistic student formation, aligning with global educational goals. The research limitations include a small, purposive sample and reliance on self-reported data, which may introduce bias. The absence of non-athlete comparisons and the retrospective nature of responses also constrain generalizability. Future study could employ mixed methods and longitudinal designs to validate findings.